PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI OPERASI HITUNG - Dwi Novita Sari; Nurhanurawati; Fitri Pratiwi Futri; Fatkhur Rohman; Wijayanti, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a Student Worksheet (LKPD) based on Problem-Based Learning (PBL) for addition and subtraction material for Grade 1 students at SDN 43 Talang Ubi. The research employed the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Expert validation results indicated that the developed LKPD has a high level of validity in terms of content feasibility (0.875), media (0.847), and graphical design (0.938). The implementation of the LKPD in the classroom showed an increase in students’ average scores from 63.07 (pretest) to 72.67 (posttest), indicating a significant improvement in mathematical concept comprehension. The PBL-based LKPD was found to be effective in enhancing student engagement and understanding of basic arithmetic operations and can serve as an innovative and enjoyable alternative learning medium to support mathematics education in elementary schools.